Keefektifan Model Model Problem Based Learning dalam Meningkatkan Kemampuan Koneksi Matematis dan Keaktifan Belajar Materi Peluang - Fefri Wahida; Andriyani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aimed to determine the effectiveness of the problem based learning model to improve mathematical connection skills and learning liveliness of probability material at SMP Negeri 14 Buton Tengah. This type of research is classroom action research with two cycles containing four action stages: planning, implementing, observing, and reflecting. The data collection technique in this study used a mathematical connection ability test, activity observation, and a questionnaire to measure student learning liveliness. The sample of this study was class VIII A and was carried out for 1 (month). The results showed average mathematical connection skills scores in the initial conditions, cycles I and II, were 24.9, 51.2, and 88.5, respectively. Meanwhile, the percentage of student learning liveliness questionnaire results in the initial conditions, cycle I, and cycle II were 50%, 58% and 84%, respectively. From the results of this study, it can be concluded that the problem based learning model is effective for improving the mathematical connections skills and student learning activities toward probability material.